The Echoing Ida Collection - Duster, Michelle; Zinzi, Janna; Alabi, Kemi; Greenlee, Cynthia R. (Book collections on Project MUSE., 2021)
"Founded in 2012, Echoing Ida is a writing collective of Black women and nonbinary writers who-like their foremother Ida B. Wells-Barnett-believe the "way to right wrongs is to turn the light of truth upon them." Their community reporting spans a wide variety of topics: reproductive justice and abortion politics; new and necessary definitions of family; trans visibility; stigma against Black motherhood; Black mental health; and more. The Echoing Ida Collection gathers the best of Echoing Ida for the first time, and features a foreword by Michelle Duster, activist and great-granddaughter of Ida B. Wells-Barnett"--